2019 IEEE 26th International Conference on Software Analysis, Evolution and Reengineering (SANER) 2019
DOI: 10.1109/saner.2019.8667987
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of Sentiments during Code Reviews: Male vs. Female

Abstract: Background: As most of the software development organizations are male-dominated, female developers encountering various negative workplace experiences reported feeling like they "do not belong". Exposures to discriminatory expletives or negative critiques from their male colleagues may further exacerbate those feelings.Aims: The primary goal of this study is to identify the differences in expressions of sentiments between male and female developers during various software engineering tasks.Method: On this goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…Research shows that women are more likely to receive negative comments and less likely to receive positive comments in their code reviews. 16 Any analysis of satisfaction with the review process should check for this in your environment. Understand that developers are likely influenced by the broader tech industry even if the patterns are not in your organization or team.…”
Section: What To Watch Formentioning
confidence: 99%
“…Research shows that women are more likely to receive negative comments and less likely to receive positive comments in their code reviews. 16 Any analysis of satisfaction with the review process should check for this in your environment. Understand that developers are likely influenced by the broader tech industry even if the patterns are not in your organization or team.…”
Section: What To Watch Formentioning
confidence: 99%
“…Fine-Grain communication looks at how the contents of messages can be examined. Paul et al looked at sentiment expression differences between men and women in code reviews [50]. They found that women are less likely to display sentiment, and that men are more likely to express negative sentiment against women developers' submissions, and more likely to withhold positive comments.…”
Section: Fine-grainmentioning
confidence: 99%
“…For example, findings show (1) significant gender differences in the features elected to use by developers and the willingness to tinker and explore features [SLR (Burnett et al 2010)], (2) men tend to switch more frequently between debugging strategies [SLR (Cao et al 2010)], (3) women tend toward underconfidence and men tend to use more unfamiliar software features [SLR ], (4) software environments are often aligned with the needs of men rather than women [SLR ; and (5) some end-user tools for debuggers may not fully support women debugging strategies [SLR (Subrahmaniyan et al 2008)]. Similarly, other studies report gender differences during code review practices indicate that (1) accepted pull requests submitted by women and men provide similar descriptions in terms of length, and generate a similar number of discussions [SLR (Imtiaz et al 2019)], (2) when both genders are known, women tend to have contributions accepted more often than men when they the contributors are from insiders to a project, but men's acceptance rates are higher when the contributors are from outsiders to a project, [SLR (Terrell et al 2017)], (3) while women concentrate their work across fewer projects and organizations, men contribute to a higher number of projects and organizations [SLR (Imtiaz et al 2019)], (4) there are gender differences in the use of positive opinion words, emoticons, and expletives during the code review as while men tend to express more positive/negative sentiments, women tend to express more neutral comments instead of expressing strong sentiments [SLR (Paul et al 2019)], and (5) men and women follow different comprehension strategies when reading source code [SLR (Zohreh Sharafi et al 2012)]. There are also gender differences in pair programming related to coordination, communication, and collaboration.…”
Section: Gender Differencesmentioning
confidence: 99%